Teaching and Researching English Accents in Native and Non-native Speakers - Waniek-Klimczak, Ewa.; Shockey, Linda R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Second language phonology is approached in this book from the perspective of data-based studies into the English sound system as used by native and non-native speakers of the language. The book offers a unique combination of psycholinguistic, sociolinguistic and pedagogical approaches, with individual contributions investigating the effect of selected conditioning factors on the pronunciation of English. With all the richness of approaches, it is a strong phonetic background that unifies individual contributions to the volume. Thus, the book contains a large body of original, primary research which will be of interest to experienced scientist, practitioners and lecturers as well as graduate students planning to embark on empirical methods of investigating the nature of the sound system.
Keywords: Linguistics; Phonology; Linguistics; Phonology